ANALISIS UNSUR INTRINSIK CERPEN “PENGEMIS DAN SHALAWAT BADAR” KARYA AHMAD TOHARI - Ujang Andri Ujang (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Short stories are part of fictional literary works based on the results of essays and human thoughts in telling a problem that is told through the characters briefly starting from the introduction, the problems to the end of the problems experienced by the characters. In general, short stories literary works tell a variety of frenzied problems of life. A short story has a constructing element, namely the intrinsic element. Intrinsic elements include theme, character, setting, characterization, style, point of view, language style and message. In this case, the researcher will analyze the intrinsic elements of Ahmad Tohari's short story entitled "Pengemis dan Salawat Badar". Researchers used a qualitative descriptive method that aims to describe the facts in a short story. Researchers are interested in analyzing this short story because it contains moral and religious messages that must be used as learning. Based on the results of the analysis, the intrinsic elements contained in this cepen, namely, the theme of the short stories related to social and religion, there are six characters and their characterizations with each different character, the plot is a progressive flow, there are three setting places and one atmosphere, perspective use the first person and the mandate teaches to be sincere and patient in every situation and always say greetings, multiply solawat praise the Prophet Muhammad.